The impacts of manipulating task complexity on EFL Learners’ Performance - Masoud Saeedi,; Saeed Ketabi,; Shirin Rahimi Kazerooni, (Penerbit UKM, 2012)
The purpose of this study is to investigate the impact of manipulating the cognitive complexity of tasks on EFL learners’ narrative task performance in terms of complexity, accuracy, and fluency of their production. To this aim, by drawing upon Robinson’s (2007) Triadic Componential Framework (TCF), four levels of task complexity were operationalized. Sixty- five Iranian students studying English as a foreign language at the intermediate level participated in this research. The obtained results revealed that manipulating different dimensions of task complexity exerts differential effects on complexity, accuracy, and fluency of learners’ narrative task performance. Additionally, it was shown that keeping tasks simple along the resource-dispersing dimension, while making them more demanding along the resource-directing dimension results in a simultaneous increase in complexity and accuracy, a finding which conforms to predictions based on Robinson’s Cognition Hypothesis. These findings suggest that task complexity can be used as a robust basis for making grading and sequencing decisions in task-based syllabi.